2013
DOI: 10.1007/s00405-013-2498-9
|View full text |Cite
|
Sign up to set email alerts
|

Vocal fold scars: current concepts and future directions. Consensus report of the phonosurgery committee of the European laryngological society

Abstract: Scarring of the vocal folds leads to a deterioration of the highly complex micro-structure with consecutively impaired vibratory pattern and glottic insufficiency. The resulting dysphonia is predominantly characterized by a reduced vocal capacity. Despite the considerable progress in understanding of the underlying pathophysiology, the treatment of scarred vocal folds is still an unresolved chapter in laryngology and phonosurgery. Essential for a successful treatment is an individual, multi-dimensional concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
113
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 119 publications
2
113
0
6
Order By: Relevance
“…[39] Medialization thyroplasty may be used to repair glottal insuffiency without directly contacting the lamina propria. [40] In addition, Hoy et al described the use of an ultra-fast laser for ablation vocal fold scar tissue. [41] Welham et al investigated the use of surgical treatments for vocal fold scar in a prospective clinical study, where they found that the thyroplasty and graft implantation methods resulted in reduced vocal handicap scores of patients with vocal fold scar, but no improvement in other assessment measures.…”
Section: Current Clinical Approaches and Evaluation Of Biomaterialmentioning
confidence: 99%
See 2 more Smart Citations
“…[39] Medialization thyroplasty may be used to repair glottal insuffiency without directly contacting the lamina propria. [40] In addition, Hoy et al described the use of an ultra-fast laser for ablation vocal fold scar tissue. [41] Welham et al investigated the use of surgical treatments for vocal fold scar in a prospective clinical study, where they found that the thyroplasty and graft implantation methods resulted in reduced vocal handicap scores of patients with vocal fold scar, but no improvement in other assessment measures.…”
Section: Current Clinical Approaches and Evaluation Of Biomaterialmentioning
confidence: 99%
“…Teflon was historically used as a more permanent material for vocal fold augmentation, but has been associated with undesirable foreign-body reactions. [40] More commonly used materials for injection for vocal fold medialization include Cymetra (collagen-based), Radiesse (calcium hydroxyapatite), and autologous fat. [40] Sataloff described autologous fat as an effective implantation for improving mucosal wave in patients with severe scar formation.…”
Section: Current Clinical Approaches and Evaluation Of Biomaterialmentioning
confidence: 99%
See 1 more Smart Citation
“…Scarring is the downstream manifestation of these injuries, and leads to incomplete mucosal wave formation and eventual dysphonia. 12,38 …”
Section: Introductionmentioning
confidence: 99%
“…1,38,53 Although improvement in rheological properties and glottal closure are observed post injection, these therapies are more supportive rather than regenerative as they do not repair associated damage with scarring and may also result in long-term complications such as chronic inflammation, implant migration, granuloma formation, and quick resorption times. 38,53 These complications necessitated the development of alternative tissue-engineered treatments for the restoration of normal vocal fold function. HA, because of its non-immunogenicity, non-antigenicity, innate biocompatibility, tunable viscoelastic properties, and ease of modification, is one of the most widely researched vocal fold tissue engineering materials.…”
Section: Introductionmentioning
confidence: 99%